Estimaciones del riesgo de liquidez de la Empresa Kineletec S.A. ubicada en Guayaquil en el periodo 2022. - Garcés Chiriguay, Jhomira Lilibeth (2023)
The objective of this case is to establish the liquidity levels of the company KINELETEC located in the Guayaquil canton, taking into account that liquidity is what allows us to identify the debt ratios and helps in decision making in the company with the optimal use of the budget prepared by the financial management in relation to a given period. The ratios and accounts that provide liquidity and the risk involved in not identifying in time the lack of cash to cover short- and long-term obligations will be identified. A good estimation of liquidity risk implies sufficient cash on hand to be able to face and drive growth in the companies. It is of utmost importance within the subject studied to know how to design or structure the possible cash projections that go according to the income received and the prompt recovery of investments, the actual development of this study will be based on the inductive deductive method because it gives us the opportunity to develop solutions according to the problems generated in the company KINELETEC. Finally, the knowledge is validated according to the theories already generated in previous studies that will serve as a basis for the complementation of the research process and generate the necessary results that favor the company with a profitability sustainability in the competitive market in which its activity is framed.